GENETIC DIVERSITY AND FRUIT QUALITY OF SEVERAL POMELO “JERUK BALI” (Citrus grandis L. Osbeck) CULTIVARS IN BALI - Mahardika, Ida Bagus Komang; Rai, I Nyoman; Mahendra, Made Sudiana; Dwiyani, Rindang (International Journal of Biosciences and Biotechnology; Vol 5 No 1 (2017)DO - 10.24843/IJBB.2017.v05.i01.p04, 2017)
This study aimed to determine the genetic diversity and fruits quality of the "Jeruk Bali" cultivars grown in Bali. This research was conducted in all regencies and city in Bali, during 2016. Furthermore, several cultivars of “Jeruk Bali” were genetically analyzed based on RAPD markers using 10 primers. Analysis of the quality of fruit is based on physical properties and chemical content. Eighteen cultivars of "Jeruk Bali" obtained have a fruit morphological character with round, short round, and piriform fruit shapes, which are red, pink, cream and white flesh color. RAPD analysis results at 53% similarity level are grouped into 5 groups. The first group was only one cultivar, the second group consisted of 13 cultivars, the third and fourth groups were only one cultivar, while the fifth group consisted of two cultivars. The analysis of the diversity between cultivars based on the combination of physical and chemical properties of the fruit with hierarchy method on similarity level about 85% in a group is obtained by 4 (four) groups. Groupings by combination of physical and chemical properties of the fruit are not synchronized in their entirety with dendograms based on their genetic diversity. This illustrates the physico-chemical properties of “Jeruk Bali” fruit in general is not fully genetical expressed, but also influenced by conditions of environmental growth.